Model of Personnel Development Through Dual Vocational Training to Promote Desirable Skills of Vocational Students - Supat Chupradit (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
The purposes of this study were 1) to study the management system context of vocational education in order to create a model of personal dual-development, and to study the effects of the development model. The research was conducted in the form of Research and Development (R&D), and was divided into three phases, as follows: Phase 1: Studying the context of vocational education dual management system in schools and workplaces; Phase 2: Formulating personal development model; and Phase 3: Studying the applications of personal dual-development model to promote desirable skills of vocational students. The samples used in this study consisted of four groups including 1) the samples used in the study of vocational education dual management system context in schools and workplaces which were teachers in schools, vocational students, and training teachers in workplaces; this samples made up 465 people and were investigated using questionnaires; 2) the samples used in creating of a personal development model including educational academics, supervisors or experienced teachers, human resources developers; this samples made up 21 people and were investigated using questionnaires; 3) the samples used in evaluating the model including teachers in schools and training teachers in workplaces; this samples made up 40 people and were investigated using questionnaires; and 4) the sample used to test the personal development model including 30 training teachers in 50 workplaces of industrial technicians in Chiang Mai and Lamphun; the tools used with this group of samples was short training process manual, test, attitude test, and satisfaction evaluation. The results were as follows. The samples gave opinions about the conditions of vocational education operation in 8 aspects, which included public relation and coordination, project implementation, curriculum, medium of instruction and facilities, human resources (personnel), learning and teaching management, measurement and evaluation, and monitoring and supervision as a whole at a high level; however, when considering aspect by aspect, the human resources (personnel) aspect received a moderate level, that was, teachers in schools, vocational students in dual system, and training teachers in workplaces lacked understanding about the Three Logics of Skills concept, which were the cognitive skills, technical skills, and behavioral skills. The samples accounted the model of personnel development through dual vocational training to promote desirable skills of vocational students that the desired attributes needed and the instruments used to develop personnel through dual vocational training to promote desirable skills of vocational students consisted in the model included 3 features, 33 attributes: the personality feature included 10 attributes, the moral feature included 13 attributes, whereas the academic and professional feature included 10 attributes. The methods used to develop those three features included short training, job training for skills improvement, and job introduction training. The implementation results of the model of personnel development through dual vocational training to promote desirable skills of vocational students revealed that teachers who participated in the training were more knowledgeable and understanding after the experiment that before and this was different at a statistical significance level of .01; whereas the training teachers had some attitudes towards the training after the experiment than before and were satisfied by the training at a high level.